Generalized Mean Square Exponential Stability for Stochastic Functional Differential Equations - Tianyu He; Zhi Li; Tianquan Feng (Mathematics)
This work focuses on a class of stochastic functional differential equations and neutral stochastic differential functional equations. By using a new approach, some sufficient conditions are obtained to guarantee the generalized mean square exponential stability for the equation under consideration. Certain existing results are refined and extended. Lastly, the validity of the main results is confirmed through several simulation examples.